The Galactic Population of Magnetars: A Simulation-based Inference Study - M. Sautron; A. E. McEwen; G. Younes; J. Pétri; P. Beniamini; D. Huppenkothen (The Astrophysical Journal)
Population synthesis modeling of the observed dynamical and physical properties of a population is a highly effective method for constraining the underlying birth parameters and evolutionary tracks. In this work, we apply a population synthesis model to the canonical magnetar population to gain insight into the parent population. We utilize simulation-based inference to reproduce the observed magnetar population with a model that takes into account the secular evolution of the force-free magnetosphere and magnetic field decay simultaneously and self-consistently. Our observational constraints are such that no magnetar is detected through their persistent emission when convolving the simulated populations with the XMM-Newton EPIC-pn Galactic plane observations, and that all of the ∼30 known magnetars are discovered through their bursting activity in the last ∼50 yr. Under these constraints, we find, within 95% credible intervals, the birth rate of magnetars to be $1.{8}_{-0.6}^{+2.6}$ kyr ^−1 , leading to having $10.{7}_{-4.4}^{+18.8}$ % of neutron stars born as magnetars. We also find a mean magnetic field at birth ( μ _b is in T) ${log}\,\left({μ }_{b}\right)=10.{2}_{-0.2}^{+0.1}$ , a magnetic field decay slope ${α }_{d}=1.{9}_{-1.3}^{+0.9}$ , and timescale ${τ }_{d}=17.{9}_{-14.5}^{+24.1}$ kyr, in broad agreement with previous estimates. We conclude this study by exploring detection prospects: an all-sky survey with XMM-Newton would potentially allow around seven periodic detections of magnetars to be obtained, with approximately 150 magnetars exceeding XMM-Newton’s flux threshold, and the upcoming AXIS experiment should allow these detections to be doubled.